Influence of Wind Direction on Thermodynamic Properties and Arctic Mixed-Phase Clouds in Autumn at Utqiaġvik, Alaska - Qiu, S; Xi, B; Dong, X (eScholarship, University of California, 2018)
Seven years of autumnal ground-based observations (September–November 2002–2008) at the U.S. Department of Energy Atmospheric Radiation Measurement North Slope of Alaska site have been analyzed for addressing the occurrence frequency and macrophysical and microphysical properties of Arctic mixed-phase clouds (AMC), as well as the relationship between environmental parameters and AMC properties. In September and October, AMC occurrence frequency is 20–30% lower during a southerly wind when compared to the other wind directions; in November, the variation of AMC occurrence frequency with wind direction is small. The mean liquid water path in November is about half of that in October and September. When the surface is snow free, temperature (T) and specific humidity (q) profiles during a northerly wind are warmer and moister than those for the southerly wind. Northerly wind profiles have a higher relative humidity to ice (RHi) and lower atmosphere stability. Furthermore, the AMC occurrence frequency has a positive relationship with RHi and a negative relationship with stability. These two points may explain the lower AMC occurrence frequency during a southerly wind. During a northerly wind, AMCs have larger radar reflectivity, wider spectrum width, and larger Doppler velocity signatures. The stronger precipitation for AMC during a northerly wind is possibly due to the cleaner air masses from the ocean (north). With the same amount of q, the radar spectrum width has a higher frequency in the larger bins during a northerly wind. Both T, q, and radar reflectivity, radar spectrum width profiles show evidence of deposition in the sub-cloud layer in September and October.